2009
DOI: 10.1016/j.mrgentox.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of oxidatively induced clustered DNA lesions in human tumor tissues

Abstract: Increased levels of oxidatively induced DNA damage have been reported in various cases of human pathogenesis like age-related and chronic diseases. Advances in experimental carcinogenesis associate high oxidative stress with genome instability and oncogenic transformation. Cancer biomarkers are helpful for early tumor diagnostics, prediction of tumor development, and analysis of individual tumors' response to therapy as well as recurrence. The repair resistant oxidatively induced clustered DNA lesions (OCDLs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 45 publications
0
57
0
1
Order By: Relevance
“…The implication of oxidative stress in genomic instability, cancer development, and cancer progression has been supported by experimental and clinical studies (24)(25)(26). Moreover, high levels of oxidative stress have been documented in cancer cells and human cancer tissues, including from PCA (12,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 95%
“…The implication of oxidative stress in genomic instability, cancer development, and cancer progression has been supported by experimental and clinical studies (24)(25)(26). Moreover, high levels of oxidative stress have been documented in cancer cells and human cancer tissues, including from PCA (12,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 95%
“…Second, Gln metabolism provides a source of reducing equivalents (NADPH) necessary to maintain GSH in its reduced state. 17 Studies have demonstrated that breast cancers show high levels of oxidative stress as verified by the detection of oxidative DNA adducts in breast cancer tissue 31 or a significant raise in oxidative stress markers in the plasma from breast cancer patients. 32 Moreover, the use of chemotherapy increases oxidative stress 33 FAC chemotherapy and radiotherapy promote further oxidative shift, which potentiate already existing chronic oxidative stress linked to breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they showed evidence of bystander or so-called distal effects [12] . In a later study, Nowsheen et al [5] showed that, in the majority of human tumor cases examined, there were higher levels of OCDLs in tumors compared with normal tissues. These data suggest for the first time the importance of endogenous non-DSB clusters in human cancer and their potential use as cancer biomarkers.…”
Section: Detection Of Ocdls In Vivo: Potential Clinical Applicationsmentioning
confidence: 92%
“…Georgakilas and his team through collaborations with various elite research groups (ECU, NCI) have taken advantage of the properties of human repair enzymes OGG1 (oxidized purines), EndoIII (oxidized pyrimidines) and APE1 (abasic sites) in order to detect a variety of bistranded OCDLs in human and mouse tissues, using adaptations of DNA gel electrophoresis [4][5][6][7][8] . The concepts in DNA cluster quantification are simple, but their execution is technically and analytically demanding.…”
Section: Detection Of Ocdls In Vivo: Potential Clinical Applicationsmentioning
confidence: 99%